DIAGNOSTIK PAPER ANALYTICAL DEVICE (PAD) MENGGUNAKAN EKSTRAK UBI JALAR UNGU UNTUK DETEKSI BORAKS DALAM MAKANAN - Rismiarti, Zuri; Indra, Asep Iin Nur; Agustini, Siti Fajarwati (Media Penelitian dan Pengembangan Kesehatan, 2024)
Consuming foods containing borax (tetraborate) will cause health problems. However, in reality, borax is often added to foods such as crackers, meatballs, wet noodles, dumplings. These foods are usually produced by unregistered public members, so their quality is less controlled, so routine monitoring of borax levels in food is needed so that the food quality circulating in the community is maintained and safe for consumption. This research aimed to develop simple method that does not use special instruments to diagnose borax using a Paper Analytical Device (PAD) based on digital imaging using natural reagents from purple sweet potato extract. The research design was laboratory research and development (RnD). The research was conducted at Poltekkes Kemenkes Bandung in January-June 2022. The samples used were borax samples at concentrations of 100, 300, and 500 ppm. The research method was PAD based on digital imaging using Image J. This research was carried out by extracting anthocyanins from purple sweet potatoes, then optimizing the anthocyanin concentration extract; pH; measurement time, determining measurement linearity, and validation by determining % recovery. The research results include that the optimum pH is 9. Optimized measurement time is 3 minutes and is stable until the 5th minute, the linear concentration range of tetraborate is 100-500 ppm tetraborate. In the validation test of the PAD method, a recovery percentage of 87.58-87.95% was obtained for 200 and 300 ppm tetraborate samples. The research result will be able to diagnose and monitor borax in food.